Fikih Kebangsaan: Sebagai Formulasi Penguatan Moderasi Beragama dan Aplikasinya di Era Digital - Solikhudin, Muhammad (Proceedings of Annual Conference for Muslim Scholars, 2023)
This paper attempts to explain national fiqh as a formulation for strengthening religious moderation in Indonesia. Indonesia is a country with the largest Muslim population in the world, but has ethnic, cultural, linguistic and religious diversity. Conflicts with racial and religious nuances are sought to be prevented as early as possible by presenting the formulation of national fiqh and its implementation in a sustainable manner. National fiqh is knowledge of religious laws and nationalism produced by ijtihad which is extracted from primary sources of Islamic law. This kind of fiqh prioritizes the human aspect, respects and appreciates diversity, because it exists in a pluralistic reality. This is of course in line with the teachings of Islam. The author also relates this study to a phenomenological approach. From this phenomenological approach, it can be understood that human actions that seek to apply National Jurisprudence and he can respect diversity on the grounds that it is ruled by religion and the State, thus bringing real harmony and happiness are meaningful actions. This is in accordance with the perspective of moderate Islam that is developing in Indonesia. Especially in the digital era, it is necessary to apply national fiqh in order to realize religious moderation in a sustainable manner.